First validation of the novel Freiburg Neurointerventional Score purposely designed for use by emergency medical dispatchers for detecting anterior circulation large-vessel occlusion in patients with suspected stroke - Erik Farin-Glattacker; Christian A Taschner; Hans-Jörg Busch; Wolf-Dirk Niesen; Matthias L Herrmann; Florian F Schuchardt; Clara Franck; Simone Meier; Max Henningsen; Friederike S Brohl; Christoph Sonntag; Nicole Wimmesberger; et al. (BMJ Neurology Open)
Background Detecting an anterior circulation large-vessel occlusion (aLVO) as a cause of stroke during emergency calls could optimise dispatch, particularly in rural areas. Numerous stroke severity scales assessing motor and cortical signs have been designed for direct patient contact; however, none have been purposely designed for emergency calls. This study aimed to prospectively validate the novel Freiburg Neurointerventional Score (FRENS) in patients presenting with a suspected acute stroke to detect aLVO.Methods Patients aged ≥18 years with suspected acute stroke brought directly to our tertiary hospital by paramedics, between May 2021 and 2022, were included in this study. We used the FRENS and National Institutes of Health Stroke Scale (NIHSS) to analyse the FRENS convergent validity. We evaluated and compared the predictive ability and test characteristics of the FRENS and five established NIHSS-based stroke severity scales for the detection of an aLVO stroke. We analysed the number of steps required for the completion of the FRENS algorithm.Results Among the 1042 analysed patients, the FRENS items showed high convergent validity with corresponding NIHSS items. A positive FRENS was statistically significantly correlated with an aLVO stroke. The FRENS had the highest sensitivity and negative predictive values for an aLVO stroke and the highest sensitivity value for M2 occlusions. The FRENS provided results after two and all four steps, in 71% and <3% of cases, respectively.Conclusions The FRENS enabled the rapid, sensitive detection of an aLVO in patients with suspected acute stroke. Designed for use in emergency calls, the FRENS requires translation and validation in a prehospital setting.